Revitalization of the Akcaya Park in Pontianak City for Green Open Space Planning - Mahardi, Putri Pratama; Alifia, Rizka; Muhtadi, Ahmad; Anggraini, Irene (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2026)
Akcaya Park is one of the open green spaces that plays an important role in providing recreational facilities, supporting social interaction, and improving environmental quality in Pontianak City. However, the park’s existing condition shows a decline in the quality of its facilities, aesthetics, and spatial utilization, making revitalization efforts necessary. This study aims to design a revitalization concept for Akcaya Park that can optimize its ecological, social, and aesthetic functions in accordance with community needs and technical standards for green open space planning.The methodology includes field surveys, collection of primary and secondary data, analysis of existing conditions, and the preparation of a design concept based on landscape planning principles and relevant technical guidelines. The design takes into account spatial arrangement, circulation, supporting facilities, lighting, vegetation, and environmental sustainability. Based on the design results, the revitalization of Akcaya Park focuses on improving accessibility, comfort, and optimizing the park’s functions, which include upgrading the children’s playground, relaxation garden, parking areas, public toilets, basketball court, waste management facilities, and lighting. This design is expected to meet community needs and contribute to the creation of a green, comfortable, and sustainable city.